Macronutrient composition of meals served to children under 6 years old in Community Child Care Centers in the Metropolitan Area of Costa Rica - Zúñiga Escobar, Marianela (2014)
Community Child Care Centers in Costa Rica represent a low cost, partially subsidized child care option for helping families living in poverty. Children from 0 to 7 years receive care and meals during the day. These centers should follow the nutritional guidelines established by the national authority to offer at least 70% of their energy needs. However, information regarding to the nutritional composition of meals offered is not well known. Objective: To evaluate the energy and macronutrient composition of lunch, morning and afternoon snacks offered in 33 community child care centers located in the metropolitan area of Costa Rica. Methods: A lunch and morning and afternoon snacks were evaluated for each child by direct weight of each meal. Results: 77% of the evaluated meals did not fulfil the recommended amount of energy. Protein did meet the recommendation for children younger than 2 years old but not for the older ones. Carbohydrate was over the recommended amount for all children, while fat was insufficient. Conclusion: Meals offered to children attending in the evaluated 33 Community Child Centers do not fulfil their energy needs. It is highly recommended to perform more in depth evaluations in order to modify current practices in these centers and to contribute to the improvement of all centers nationwide. Updated support materials for community mothers are needed to achieve and develop menu cycles and to offer portion size meals according to the needs of the population they serve.